2005
DOI: 10.1017/s0021859605005496
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genotype and environment on seed yield and quality of rice

Abstract: SU MMARYSeed yield and seed quality determine much of the value of rice (Oryza sativa L.) crops to the producers. The effects of genotype and environment on seed yield and quality were investigated using 12 rice genotypes grown during 3 years (2000)(2001)(2002)(2003) at four different sowing dates in India, where detailed environmental data were collected. Yield, seed weight, proportion of seed setting and quality in terms of potential seed longevity, proportion of discoloured seeds, seed leachate conductivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 15 publications
3
30
0
1
Order By: Relevance
“…7 Change in rice equivalent yield of rice-peanut cropping systems with medium duration cultivar (MP) for future years (2020, 2050 and 2080) under A2 and B2 climate change scenarios for different planting time as compared to base period with normal planting (15 Jul./9Feb) at different locations (Kharagpur, Cuttack, East Godavari and Vizianagaram) in India on rice yield. Similar results about sensitivity of spikelet sterility to flowering were reported by many researchers (Yoshida 1981;Krishnan and Surya Rao 2005;Jagadish et al 2008). Similarly for peanut, high temperature during flowering can be avoided by advancing the sowing time.…”
Section: Evaluation Of Adaptation Measuressupporting
confidence: 85%
“…7 Change in rice equivalent yield of rice-peanut cropping systems with medium duration cultivar (MP) for future years (2020, 2050 and 2080) under A2 and B2 climate change scenarios for different planting time as compared to base period with normal planting (15 Jul./9Feb) at different locations (Kharagpur, Cuttack, East Godavari and Vizianagaram) in India on rice yield. Similar results about sensitivity of spikelet sterility to flowering were reported by many researchers (Yoshida 1981;Krishnan and Surya Rao 2005;Jagadish et al 2008). Similarly for peanut, high temperature during flowering can be avoided by advancing the sowing time.…”
Section: Evaluation Of Adaptation Measuressupporting
confidence: 85%
“…Previous studies showed that the seed weight of rice was influenced more by genotypic than by environmental factors. [19] The moisture content (MC) in P14 was the highest with a value of 13.92 %, and conversely, the lowest MC of 7.01 % was in P2. A wide range in seed volume (SV) was from 202.13 mm 3 to 498.46 mm 3 , and the P14 seeds were significantly bigger than others.…”
Section: Phenotypic Characteristics Of the Seedsmentioning
confidence: 97%
“…Генетика признака практически не исследована (Агарков, Касьянов, 2002; Рябушкина, 2005; Дымова, Головко, 2007; Шахба-зов, 2007; Гончарова, 2013). Однако известно, что наряду с уровнем температуры важное значение имеет продол-жительность ее воздействия на растения и относительная влажность воздуха (Krishnan et al, 2005;Mackill et al, 1982). Жароустойчивость различных видов обусловлена различными механизмами (интенсивной транспирацией, отражательными свойствами поверхности, способностью усиливать биосинтез белков «теплового шока», актив-ностью транскрипционно-трансляционной системы и т.…”
Section: адаптивность к высоким температурамunclassified